Phenotypic data related to seedling traits of hexaploid spring wheat panel evaluated under salinity stressMendeley Data - Santosh Gudi; Harsimardeep S Gill; Serena Collins; Jatinder Singh; Devinder Sandhu; Sunish K Sehgal; Upinder Gill; Rajeev Gupta (Data in Brief)
Salt stress is a major abiotic stress affecting wheat at various developmental stages and significantly reduces grain yield. Developing salt resilient wheat cultivars alleviate the negative impacts of salt stress and helps in maintaining sustainable grain yield under salt stress. A study was undertaken to assess the response of various seedling traits in a genetically, phenotypically, and geographically diverse panel of 228 hexaploid spring wheat accessions using greenhouse lysimeter system with two irrigation treatments: control (electrical conductivity of irrigation water as deci-Siemens per meter., (ECiw = 1.46 dSm−1) and saline (ECiw = 14 dSm−1). Salt stress was given on 18 days old seedlings and the targeted salinity level (ECiw = 14 dSm−1) was achieved gradually over two days period, to overcome any osmotic shock. Data on various seedling traits [such as shoot height (SH; inches), root length (RL; inches), tiller number (TN), shoot weight (SW; grams), and root weight (RW; grams)] were collected after three weeks of salt treatment from control and salt stress environment. Shoot and root traits were used to calculate root length by shoot height (RL-by-SH) and root weight by shoot weight (RW-by-SW) ratios. Furthermore, the salt tolerance index (STI), was calculated for each trait by dividing trait values of each accession from salt-treated tanks by those from control tanks. Raw data was subjected to mixed linear analysis to derive best linear unbiased prediction (BLUP). BLUP values were also used for Pearson’s correlation coefficient analysis and principal component analysis (PCA), which gives intrinsic relationship among various seedling traits. Dataset presented here is a valuable source for identifying tolerant lines for salt stress environment. Moreover, researchers can utilize this information to identify potential genomic regions associated with salt stress tolerance and can be utilized in developing salt resilient wheat cultivars.